THE EMISSION AND VERTICAL FLUX OF PARTICULATE MATTER <10 μM FROM A DISTURBED CLAY-CRUSTED SURFACE - Houser Ch.A.; Nickling W.G. (My University, 2001)
Arid and semi-arid environments are important sources for the atmospheric loading of PM10 (particulate matter <10 μm), although the emission of this material is often limited by surface crusts. study investigates and vertical flux pm10 from a clay-crusted playa, with and without saltating grains to abrade the surface. Using a portable field wind tunnel, it was found that, despite disturbance to the surface, the emission of PM10 decays rapidly without abrasion. Only in the presence of saltating grains was PM10 continuously liberated from the surface, such that the emission rate (the total amount of PM10 emitted from the surface expressed as a horizontal flux) varied linearly with the saltation transport rate. Although the emission of PM10 was found to depend on saltation abrasion, past studies have tended to focus on the relationship between the vertical flux of PM10 (the amount of PM10 being transported vertically through the boundary layer) and the shear velocity. In this study, the vertical flux of PM10 was found to vary with the shear velocity to the power of 2·14. Although the vertical PM10 flux is a proportion of the emission rate (the horizontal flux), no statistically significant relationship was observed between the emission rate and the shear velocity. The disparity of these results is explained by the lack of a consistent relationship between the shear velocity and the saltation transport rate in this supply-limited environment. This suggests that the observed relationship between the vertical PM10 flux and the shear velocity is a spurious correlation, resulting from the use of shear velocity to calculate the vertical dust flux. It is thus concluded that shear velocity is not an appropriate variable for emission modelling in supply-limited environments and that improvements in dust emission modelling will only be realized if the abrasion process is the focus of a concerted research effort.
Keywords: EMISSION RATE; PM10; SALTATION TRANSPORT; VERTICAL DUST FLUX